Perancangan Interior Pusat Fashion Forever 21 di Surabaya - Sriti Mayang Sari, Anastasia Leony Kristanto (Intra, 2014)
Surabaya is one of the biggest cities in Indonesia. Most people whose life there has a consumptive life style, especially for those women. Surabaya has much fashion retails with its brands and facilities. But it still canât fulfill what customers needs.So, with this Interior Design Fashion Center âForever 21â in Surabaya hope can fulfill what customers needs and also can give them a new shopping experience. Forever 21 is a brand which already available in Jakarta and get positive responses from people there. Because the design concept is showing a new and interesting store, and also give a happy atmosphere for customers. This concept âll be applied at display shape and interior element. This project âll be supported with information center, so that people can get information about brand and fashion trend.